SCIDOT-37. ASSESSING CEREBROSPINAL FLUID FLOW DYNAMICS IN PEDIATRIC PATIENTS WITH CENTRAL NERVOUS SYSTEM TUMORS. (11th November 2019) - Kramer, Kim; Donzellie, Maria; Nwora, Emmanuela; Pandit-Taskar, Neeta
Abstract: BACKGROUND: The incidence of abnormal CSF flow dynamics in the pediatric population with CNS tumors prior to intraventricular therapy has not been described. METHODS: We performed a single-institution, retrospective review of patients with primary or metastatic CNS tumors treated between 2003–2018 (15 years).. Patients underwent 111-indium diethylene triamine pentaacetic acid injection into the CSF intraventricular space followed by nuclear medicine imaging at 90 minutes, 4, 24, and 48 hours (if required). CSF flow was classified as normal, delayed, asymmetric or obstructed. RESULTS: 278 CSF flow studies were performed in 224 patients, 202(90%) <18 years of age. 116(52%) patients had metastatic CNS neuroblastoma, 57(25%) had medulloblastoma, and 51(23%) had other CNS histologies. Of the 278 studies, 237(85%) were normal, 9(3%) required neurosurgical intervention, 25(9%) were delayed, and 7(3%) were asymmetric. CONCLUSIONS: Abnormal CSF flow and necessity of neurosurgical intervention must be considered when attempting to ensure appropriate intraventricular therapy in the pediatric population.